Methodical Approach to Selecting the Appropriate Distribution for Reliability Analysis: Automotive Application - Bella Naoufal; Salhi Nohaila; Lagrat Ismail (E3S Web of Conferences)
In this study, we propose a methodical approach to selecting an appropriate statistical distribution for reliability analysis. In this approach, we have defined a methodology for testing reliability distributions based on the Kolmogorov Smirnov K-S test for MTBF Data collected from Self-Diagnostic of a sample of 50 critical components part of a complex automotive system. Finally, we proposed two solutions: the first involves migrating from one distribution to another according to the intervals, and the second allows for the selection of the distribution that is representative over a maximum number of intervals. These strategies were developed from the analysis of results after application of the K-S test on the distributions tested. This approach will contribute. to the reliability analysis of complex systems. As a result, in improving the models used to analyze complex systems behavioral analogies such as Petri nets or Markov chains.